The pattern of fall of serum bilirubin after operative relief of obstructive jaundice. A preliminary report (2010)
This is the beginning of a prospective study on patients who have obstructive jaundice to see how the serum bilirubin falls after operative relief of the obstruction. Seven of such patients have been studied; four had carcinoma of the head of the pancreas while the other three had choledocholithiasis. The patients with carcinoma had relief of the jaundice through a biliary-enteric anastomosis and those with common bile duct stones had choledochotomy with stone extraction which was completed with insertion of a T-tube. Serial bilirubin estimations were then performed post-operatively to chart the pattern and rate of descent of this in each patient. Our observations suggest that the pattern of fall of serum bilirubin after successful decompression of the extra-hepatic biliary tree exhibit a distinct pattern regardless of the surgical procedure performed for the relief of the obstruction.